2014
DOI: 10.21693/1933-088x-13.2.81
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory Hemodynamic Monitoring in the Management of Pulmonary Arterial Hypertension

Abstract: Background: Pulmonary arterial hypertension (PAH) is characterized by pulmonary vascular remodeling, rise in pulmonary arterial pressures, and if left untreated, right heart failure. Invasive hemodynamic assessment with right heart catheterization (RHC) has been the gold standard for the diagnosis and serial assessment of patients with PAH. However, RHC has important limitations and might be supplemented by newer technologies in the management of PAH patients. Implications for Clinicians: Implan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…Its invasive nature precludes its regular use in clinical practice. Newer technologies could overcome this limitation providing periodical measurement of pulmonary arterial systolic, diastolic and mean pressures and of cardiac output assessed through a validated algorithm [ 54 ]. In this regard, Benza et al recently evaluated the feasibility and early safety of monitoring PAH patients using an IHM implanted in a distal branch of the pulmonary artery, previously tested in patients with heart failure [ 55 ].…”
Section: Telemedicine In Pah: Current Available Tools and Future Chal...mentioning
confidence: 99%
“…Its invasive nature precludes its regular use in clinical practice. Newer technologies could overcome this limitation providing periodical measurement of pulmonary arterial systolic, diastolic and mean pressures and of cardiac output assessed through a validated algorithm [ 54 ]. In this regard, Benza et al recently evaluated the feasibility and early safety of monitoring PAH patients using an IHM implanted in a distal branch of the pulmonary artery, previously tested in patients with heart failure [ 55 ].…”
Section: Telemedicine In Pah: Current Available Tools and Future Chal...mentioning
confidence: 99%
“…Conversely, right heart catherization allows for a comprehensive hemodynamic assessment, but it is an invasive procedure with technical challenges, and it must be performed in a clinic, providing a snapshot of patient’s hemodynamics at a single time point. Ambulatory IHMs, such as CardioMEMS TM (Abbott, Sylmar, CA, USA), providing frequent remote hemodynamic measurements in the home setting and recording the variability of pulmonary pressure during the day, provide additional information for PAH patients’ management, potentially overcoming the above limitations [ 22 ].…”
Section: Novel Devices For Monitoring Pulmonary Arterial Hypertension Patientsmentioning
confidence: 99%
“…Conversely, the experience of IHMs in the management of patients with PAH is still limited to small series. CardioMEMS system implantation in 26 PAH patients with NYHA class III or IV has recently shown that IHMs may represent a promising tool to early identify decompensation or noncompliance, to reassess response to therapy and to allow rapid drug titration, reducing in-person visits and invasive hemodynamic assessments [ 22 , 26 ]. Importantly, while clinical experience with IHMs in PAH is increasing, providing a huge amount of data, IHMs represent a unique opportunity to improve and validate computational cardiovascular simulators in this setting.…”
Section: The Cardiomems Systemmentioning
confidence: 99%
“…As described in the main articles of this issue of Advances, 3 new oral medications were approved in 2013, 2,3 and implantable hemodynamic monitoring and implantable pump delivery systems are poised to change our understanding of disease severity, response to treatment, as well as delivery of intravenous prostacyclin. 3,4 There is also news regarding additional treatments in the therapeutic pipeline and recent data supporting firstline double 5 and triple combination 6 medication therapy. These developments are raising the question: is the economic burden of treating PAH continually increasing, and if so, is it worth the additional cost?…”
mentioning
confidence: 99%